A home for goddesses and dogs - Connor, Leslie (Katherine Tegen Books, 2020)
After her mother dies, thirteen-year-old Lydia moves into a Connecticut farm with Aunt Brat, her wife Eileen, and the elderly live-in landlord Elloroy. Upon her arrival, Aunt Brat adopts a rescue dog who can't seem to stay out of trouble. Lydia struggles to cope with her mother's death, a new school, and a lovable, yet terrible, dog--all while keeping her secrets intact.